Healthier societies from analysis to action - Heymann, Jody, 1959- (New York ; Oxford : Oxford University, 2006)
Extensive research has shown that social factors are as important as biological ones in determining health. This work addresses the fundamental questions which will lead the way toward countries investing seriously in improving social conditions, as a way of improving population health.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social medicine; Medical policy -- Social aspects; Epidemiology; Social change; Medical geography